The impossibility of the rule of law - Endicott, T (Oxford University Press, 1999)
No community fully achieves the ideal of the rule of law. Puzzles about the content of the ideal seem to make it necessarily unattainable (and, therefore, an incoherent ideal). Legal systems necessarily contain vague laws. They typically allow for change in the law, they typically provide for unreviewable official decisions, and they never regulate every aspect of the life of a community. It may seem that the ideal can never be achieved because of these features of legal practice. But I ask what counts as a 'deficit' in the rule of law, and I argue that none of these features of legal practice necessarily amounts to a deficit. I conclude that communities fail to achieve the rule of law only because of official infidelity to law, and the failure of lawmakers to pursue the ideal (or their decision not to pursue it). The rule of law is not necessarily unattainable.